Demographic Factors, Financial Self-Efficacy, And Financial Independence of Young Adults in Surabaya - Evelyn, Evelyn (IJEBD (International Journal of Entrepreneurship and Business Development), 2023)
Purpose : One of the key characteristics that can indicate a person's maturity is financial independence. Unfortunately, not many young adults in Indonesia are successful to become financially independent. Thus, the purpose of this study is to examine the variables that may have an impact on young adults’ financial independence. Design/methodology/approach : 118 Surabaya-based young adults served as the study's respondents. Distribution of questionnaires was used to collect data, which was then processed using logistic regression. Findings : The findings of this study demonstrate that age, education, marital status, and self-efficacy all have an impact on young adults' financial independence. It is expected that the findings of this study will help those involved in the attempt to increase financial independence among Indonesian young adults. Furthermore, it is expected that this research will contribute to ongoing studies on financial independence. Paper type : research paper